In silico Probing Ca2+ And Zn2+ Permeable Transmembrane 4Aβ1-42 Barrel - Ngo, Son Tung (Communications in Physics, 2021)
Alzheimer’s disease is known as one of the most popular forms of dementia affecting numerous people worldwide. The Amyloid beta (Aβ) peptides form to oligomeric conformations that cause the intracellular Ca2+ and Zn2+ abnormality leading to the death of neuron cells. The failure of AD therapy targeting Aβ oligomers probably caused by misunderstanding the ions transport through transmembrane Aβ (tmAβ) ion-like channel since Aβ oligomers transiently exist in a mixture order of Aβ oligomers. The high-resolution of tmAβ peptides are thus unavailable until the date. Fortunately, computational approaches are able to complement the missing experimental structures. The transmembrane 4Aβ1-42 (tm4Aβ1-42) barrel, one of the most neurotoxic elements, was thus predicted in the previous work. Therefore, in this context, the Ca2+/Zn2+ ions transport through the tm4Aβ1-42 barrel was investigated by using the fast pulling of ligand (FPL) and umbrella sampling (US) methods. Good consistent results were obtained implying that Ca2+ ion transport through tm4Aβ1-42 barrel with a lower free energy barrier compared with Zn2+ ion. The obtained results about Ca2+/Zn2+ transport across tmAβ1-42 barrel probably enhances the AD therapy